Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1159/000082976
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of VEGF-Induced Uterine Venous Hyperpermeability

Abstract: Background: Transfer of molecular signals from veins to adjacent arteries is an established mechanism of vascular communication in the uterine circulation, which ultimately depends on venous permeability. This study tests the hypotheses that: (1) uterine veins are permeable to intravenous solutes, using a 3-kDa dextran tracer and (2) this permeability is enhanced in response to vascular endothelial growth factor (VEGF). Additionally, the involvement of nitric oxide (NO), calcium, and the phospholipase C-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Several related studies from our laboratory have shown that molecules as large as 70 kDa pass across the uterine venous wall, and that this process is augmented in pregnancy due to the increased wall tension present in the enlarged veins 28. Moreover, this process can be amplified considerably by intravenous VEGF, and is therefore subject to regulation29. Future studies will address this issue of pathway further, and at this point its involvement still remains hypothetical with regard to the circumferential remodeling of uterine artery in vivo .…”
Section: Discussionmentioning
confidence: 96%
“…Several related studies from our laboratory have shown that molecules as large as 70 kDa pass across the uterine venous wall, and that this process is augmented in pregnancy due to the increased wall tension present in the enlarged veins 28. Moreover, this process can be amplified considerably by intravenous VEGF, and is therefore subject to regulation29. Future studies will address this issue of pathway further, and at this point its involvement still remains hypothetical with regard to the circumferential remodeling of uterine artery in vivo .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, our results showed no increased expression of VEGFRs in the cerebral veins and also no increase in BBB permeability. This could reflect a possible protective mechanism in the brain compared to the uterine circulation that requires increased vascular permeability for controlled extravasation of intravenous molecules in the maternal-fetal unit (42), while the BBB must maintain its protective state to prevent brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the effective dosages causing dilation range from 10 to 1,000 p M [5,6,7,8,35,36,37,38,39]. Permeability changes and migration/proliferation effects with VEGF-A or FGF2 occur over this same range, although frequently much higher concentrations have been tested [4,34,35,40,41,42,43,44,45,46,47,48,49]. Thus, key physiological effects of growth factors (dilation, permeability, migration/proliferation) are elicited by similar concentrations in the p M range.…”
Section: Discussionmentioning
confidence: 99%
“…This value of Jv/S is of the same order of magnitude that can be found in the literature for exposure to VEGF-A (50 ng/ml or 1 n M ). Within seconds, VEGF-A increases hydraulic conductivity 2- fold [4], increases small solute (3 kD) permeability 3.3-fold [40], and in the hamster cheek pouch, large solute (150 kD) permeability is elevated as much as 10-fold at this dose [35]. Using a basal value for Lp of 2×10 –7 cm·s –1 ·cm·H 2 O –1 [4], and conservatively only doubling Lp with VEGF-A exposure to 4 × 10 –7 cm·s –1 ·cm·H 2 O –1 , at a constant net pressure of 30–50 cm H 2 O [4], Jv/S would be 6 to 10 × 10 –6 cm/s.…”
Section: Discussionmentioning
confidence: 99%